Ketersediaan Akomodasi Wisata di Kabupaten Jepara dalam Mendukung Perwujudan Daerah Tujuan Wisata Unggulan - Rizqita Shofa Nida; Landung Esariti (Teknik PWK (Perencanaan Wilayah Kota), 2023)
Jepara is one of the regions that have a lot of tourist destinations in Central Java. This is due to its location which borders the Java Sea and is close to Mount Muria. The development of existing tourism potential needs to be supported by tourist facilities, especially tourist accommodation. Moreover, tourist accommodation is indispensable since the rise of the staycation trend in this sector. This article aims to identify the availability of tourist accommodation in Jepara Regency using a mixed-method with a descriptive approach. Two analyzes were used, the first was tourist characteristics and preferences analysis. Second, analysis of the characteristics of tourist accommodation in Jepara Regency. The results of this study state that there are enough tourist accommodations in Jepara Regency to support tourism activities. However, the existing accommodation tends to agglomerate in only one area, especially in Jepara, Tahunan, and Mlonggo sub-districts. This research recommends that the government of Jepara Regency can create tourism development directions that can create equitable development of tourism in other tourist areas in Jepara. So that the development of tourism and tourist accommodation in the future will not only agglomerated in one area.